THE INFLUENCE OF HEALTH EDUCATION ON DROUGHT DISASTER MITIGATION KNOWLEDGE - Rahmayanti, Yeni Nur; Utomo, Wahyu; Cahyaningtyas, Anindhita Yudha (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Disaster health education is included in disaster mitigation which aims to increase public knowledge and minimize casualties caused when a disaster occurs. School-aged children are a vulnerable group who are still unfamiliar with disaster knowledge, so there is a need for health education about disasters. The aim of the research is to determine the influence of health education on students' knowledge of drought disaster mitigation. This research uses a Pre-Experimental research type that uses a One-Group Pre-Test and Post-Test Design, and uses a total sampling technique with a sample size of 46 respondents. The results of the research before being given health education showed that 29 (63.0%) respondents were at a good level of knowledge with an average score of 10.17. The research results after being given health education increased students' knowledge level, namely 41 (89.1%) respondents had good knowledge with an average score of 11.93. The data analysis used was the Wilcoxon test, with a significance level of a=0.05, the result was r 0.000<a so that H0 was rejected and Ha was accepted. From these results it can be concluded that there is an influence of health education on students' knowledge of drought disaster mitigation.